Ecological Support for Deaf People in Viet Nam: Analysis of Inclusion and Barriers - Tran, Dai Phuoc (Philippine Social Science Journal, 2025)
Framed by the UN Convention on the Rights of Persons with Disabilities, this qualitative study analyzes the challenges surrounding the educational and social inclusion of deaf persons in Vietnam. Drawing on interviews with 40 participants across Vinh Long and Da Lat, the research examines ecological dimensions—family, school, and community—to highlight critical gaps in policy enforcement, communication, and support resources. Results indicate that while elementary education offers some promise, support services diminish significantly during high school and adulthood, leaving families to face immense struggles despite existing legal protections. By exposing these fragmented systems, the study advocates for integrating social work professionals into educational and workplace settings and underscores the urgent need for a comprehensive research program to address the systemic barriers facing individuals with hearing impairments throughout their lives.